CORRELATION BETWEEN GLOMERULAR FILTRATION RATE AND CALCIUM AND PHOSPHATE LEVELS IN PREDIALYSIS CHRONIC KIDNEY DISEASE PATIENTS AT PROF. DR. I.G.N.G. NGOERAH GENERAL HOSPITAL - Raharja, Ananda Eka; Surudarma, I Wayan; Wiryanthini, Ida Ayu Dewi; Sutadarma, I Wayan Gede (E-Jurnal Medika Udayana, 2025)
Chronic Kidney Disease (CKD) is a disease that occurs due to structural and functional alterations in the kidney for more than 3 months. Glomerular Filtration Rate (GFR) is the best parameter used to measure kidney function. The decline in kidney function leads to changes in mineral levels, particularly calcium and phosphate. The purpose of this study is to determine the correlation between GFR and calcium and phosphate levels in pre-dialysis CKD patients at Prof. dr. IGNG Ngoerah General Hospital Denpasar. This study used an analytical observational design with a cross-sectional study on 50 pre-dialysis CKD patients who were treated at Prof. dr. IGNG Ngoerah General Hospital Denpasar in 2021-2022, fulfilling inclusion and exclusion criteria. The correlation between GFR and calcium and phosphate levels was analyzed using Spearman correlation test. The patients were mostly males (64%), with a median age of 59.5 (21-70) years, and the majority in stage 5 (70%). The median GFR value was 6.57 (1.78-56.86) mL/minute/1.73m², the mean calcium level was 8.22 ± 0.83 mg/dL, and the median phosphate level was 4.94 (2.85-12.07) mg/dL. The Spearman correlation result between GFR and calcium levels was not significant ( r = 0.131, p = 0.365) and between GFR and phosphate was significant ( r = -0.527, p = 0.000). The conclusion is there was no significant correlation between GFR and calcium levels, but there was a significant moderate correlation between GFR and phosphate levels in pre-dialysis CKD patients in this study. Keywords : Glomerular Filtration Rate, Calcium, Phosphate